2020
DOI: 10.1111/ene.14277
|View full text |Cite
|
Sign up to set email alerts
|

Does SARS‐Cov‐2 invade the brain? Translational lessons from animal models

Abstract: The current coronavirus disease (COVID‐19) outbreak, caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), has raised the possibility of potential neurotropic properties of this virus. Indeed, neurological sequelae of SARS‐CoV‐2 infection have already been reported and highlight the relevance of considering the neurological impact of coronavirus (CoV) from a translational perspective. Animal models of SARS and Middle East respiratory syndrome, caused by structurally similar CoVs dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
242
0
19

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(275 citation statements)
references
References 57 publications
4
242
0
19
Order By: Relevance
“…On the other hand, the idea that SARS-CoV-2 could infect the brain through peripheral nerves, and specifically an olfactory route, has been raised by several authors, both in light of the anosmia observed in COVID-19 patients (40,41) and from experimental animal studies on SARS-CoV (42,43). In the latter, SARS-CoV administered intranasally was found in the hypothalamus and brainstem within days, a determining factor for mortality (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the idea that SARS-CoV-2 could infect the brain through peripheral nerves, and specifically an olfactory route, has been raised by several authors, both in light of the anosmia observed in COVID-19 patients (40,41) and from experimental animal studies on SARS-CoV (42,43). In the latter, SARS-CoV administered intranasally was found in the hypothalamus and brainstem within days, a determining factor for mortality (43).…”
Section: Discussionmentioning
confidence: 99%
“…Once in the bloodstream, the virus could also access other parts of the brain through a leaky endothelial barrier, or other CVOs such as the organum vasculosum of the lamina terminalis, the subfornical organ or the area postrema (35), all of which play key roles in either the risk factors or the physiological functions targeted by SARS-CoV-2. While the AHBA does not allow gene expression in these CVOs to be analyzed, further immunolabeling experiments may provide evidence for viral targeting.On the other hand, the idea that SARS-CoV-2 could infect the brain through peripheral nerves, and specifically an olfactory route, has been raised by several authors, both in light of the anosmia observed in 41) and from experimental animal studies on 43). In the latter, SARS-CoV administered intranasally was found in the hypothalamus and brainstem within days, a determining factor for mortality (43).…”
mentioning
confidence: 99%
“…The animal studies also provided hints for the potential routes of CNS entry, i.e. olfactory bulbs, peripheral nerves, synapseconnected route from the lungs to the medullary cardiorespiratory center and hematogenic spread [4]. The animal experiments furthermore identified that features of CoV CNS infection include a key role for the innate immune system, impact of aging and an earlier viral clearance in animal models.…”
mentioning
confidence: 89%
“…To fill this knowledge gap about the potential neuroinvasiveness and route of central nervous system (CNS) entry, Silvia Natoli and collaborators went back to the scientific literature on animal models of SARS-CoV and Middle East respiratory syndrome virus [4]. They studied whether there is evidence for neuropathogenesis in experimental studies of these structurally similar CoVs, which were responsible for the epidemics with severe respiratory disease in 2002 and 2012, respectively.…”
mentioning
confidence: 99%
“…SARS-CoV2 requires the angiotensinconverting enzyme 2 (ACE2) to enter cells. This receptor is expressed in endothelial cells and neurons, which indicates that it has neuroinvasive potential [4].…”
mentioning
confidence: 99%